Vitamin B12 deficiency newborn screening - Mütze, Ulrike; Gleich, Florian; Haas, Dorothea; Urschitz, Michael S.; Röschinger, Wulf; Janzen, Nils; Hoffmann, Georg F.; Garbade, Sven; Syrbe, Steffen; Kölker, Stefan (Pediatrics, 2024)
Vitamin B12 deficiency (VitB12D) might cause neuro-developmental impairment in the first year of life. Newborn screening (NBS) for VitB12D was shown to be technically feasible and early treated infants developed favorably. This study aims to evaluate the impact of NBS in prevention of symptomatic infantile VitB12D.In a nationwide surveillance study in cooperation with the German Pediatric Surveillance Unit, incident cases with VitB12D (<12 months of age) were prospectively collected from 2021 to 2022.In total, 61 cases of VitB12D reported to German Pediatric Surveillance Unit were analyzed, either identified by NBS (N = 31) or diagnosed after the onset of suggestive symptoms (non-NBS; N = 30). Ninety percent of the infants identified by NBS were still asymptomatic, whereas the non-NBS cohort presented at median 4 month of age with muscular hypotonia (68%), anemia (58%), developmental delay (44%), microcephalia (30%), and seizures (12%). Noteworthy, symptomatically diagnosed VitB12D in the first year of life was reported 4 times more frequently in infants who did not receive NBS for neonatal VitB12D (14 in 584 800) compared with those screened for VitB12D as newborns (4 in 688 200; Fisher's Exact Test, odds ratio 4.12 [95% confidence interval: 1.29-17.18], P = .008). The estimated overall cumulative incidence was 1:9600 newborns per year for neonatal VitB12D and 1:17 500 for symptomatic infantile VitB12D.NBS for neonatal VitB12D may lead to a fourfold risk reduction of developing symptomatic VitB12D in the first year of life compared with infants without NBS.